ANALISIS KESEHATAN BIBIT EKALIPTUS (Eucalyptus Pellita) DI PERSEMAIAN PT. IKA PASTI SEJAHTERA - Maulida Rohmi; Normela Rachmawati; Damaris Payung (Jurnal Sylva Scienteae, 2026)
Eucalyptus (Eucalyptus pellita) is one of the priority forest plant types for the development of industrial Plantation Forest (HTI) programs. One of the concerns in the maintenance of eucalyptus is maintaining the health of seedling to ensure optimal growth. One way to produce high-quality seedlings is to improve the source of seedlings through nurseries. The research aims to analyse damage to eucalyptus seedlings, calculate the intensity of pest and disease attacks and the percentage of damage to eucalyptus seedlings. The method applied in this research is the scoring method by determining the attack value on eucalyptus seedlings. The result of this study show that the types of damage to eucalyptus seedlings are leaf spots, yellowing leaves, drying leaves, hollow leaves, stunted, dead and a combination of several damages. The intensity of pest and diseases attack of 41,46% indicates that seedlings are categorised as moderately damaged and the overall percentage of seedling damage is 100%.